Specification for electrically-heated catering equipment Part 5. Steaming ovens (BSI, 1969)
Cookers, Cooking appliances, Steaming (cooking), Ovens (cooking appliances), Catering equipment, Electrically-operated devices, Type testing, Testing conditions, Visual inspection (testing), Scratch tests, Rated voltage, Marking, Endurance testing, Test equipment, Electrical testing, Earthing, Temperature-rise limit, Thermal testing, Electrical insulation, Dielectric-strength tests, High-voltage tests, Mechanical testing, Impact testing, Thermostats, Flexible conductors, Electric terminals, Leakage paths, Clearance distances, Corrosion tests, Circuits, Cooking, Performance testing